Efektivitas Dua Model Intervensi Medication Therapy Management (MTM) dalam Meningkatkan Pengetahuan, Kepatuhan, dan Luaran Klinis pada Pasien Hipertensi - Perangin-angin, Arihta Sri; Harahap, Urip; Dalimunthe, Aminah (Journal of Pharmaceutical and Sciences, 2026)
Hypertension is a major contributor to morbidity and mortality in Indonesia and worldwide. The success of hypertension therapy is strongly influenced by patient knowledge and medication adherence. The 2023 Indonesian Health Survey reported a hypertension prevalence of 30.6% among adults, with a prevalence of 24.4% in North Sumatra. Medication Therapy Management (MTM) represents a strategic approach to optimizing hypertension treatment outcomes. This study aimed to evaluate two MTM intervention models—direct interaction and audio-visual—and assess their effects on knowledge, medication adherence, and clinical outcomes among hypertensive patients at the Aviati Clinic, Medan. This quasi-experimental comparative study employed a three-group pretest–posttest design involving 126 hypertensive patients. Participants were allocated into a control group receiving usual care without structured education, a direct interaction MTM group, and an audio-visual MTM group. Patient knowledge was assessed using the HKLS questionnaire, adherence was measured using the MARS-5 questionnaire, and clinical outcomes were evaluated through blood pressure measurements. Data were analyzed using the Kruskal–Wallis test followed by Bonferroni post hoc analysis. The results demonstrated that both MTM intervention models significantly improved knowledge, medication adherence, and clinical outcomes compared with the control group (p < 0.001). Although both intervention groups were effective, the direct interaction MTM model produced a greater reduction in systolic blood pressure than the audio-visual intervention. These findings indicate that structured MTM interventions, particularly those delivered through direct interaction, are effective in improving therapeutic outcomes in patients with hypertension.